Basic Principles of Using Bank Plastic Cards and International Payment Systems in Uzbekistan - Mahliyo Diyorova; Urinov Komil (Zien Journals, 2022)
This article describes the analysis of the use, shortcomings and achievements of bank plastic cards in the Republic of Uzbekistan
Keywords: Mastercard; Visa; UZCARD; Humo